Synthesis of 4-thiol-furanosidic uronate via hydrothiolation reaction. Issue 30 (21st May 2021) - Ma, Shih-Ting; Lee, Chia-Wei; Liu, Wei-Min
Abstract : Uronic acids are not only important building blocks of bioactive molecules but also are widely used in the food and pharmaceutical industries. Its derivative, 4-thiol-furanosidic uronate was successfully synthesized and firstly reported here. Abstract : Uronic acids are not only important building blocks of polysaccharides and oligosaccharides but also are widely used in the food and pharmaceutical industries. Inspired by the structure of natural products, here, we disclosed base-mediated and radical-mediated hydrothiolation reactions for the preparation of thiol-contained uronates. In comparison with base-mediated reaction, radical-mediated hydrothiolation is inefficient due to the electron-withdrawing group on the ethylene group; nevertheless, the adduct had excellent stereoselectivity at both C-4 and C-5 positions. For the alkaline approach, thiols as nucleophiles can regioselectively and stereoselectively attach to the C-4 position of Δ- 4, 5 -unsaturated uronate with moderate to good yields. However, poor stereoselectivity at the C-5 position was observed due to retro thiol-Michael addition. After removing the protecting group of the thiol, the thiol adduct was isomerized to the furanosidic form and the 4-thiol-furanosidic uronate derivative was synthesized for the first time.